Manajemen Bank Syariah Dalam Upaya Pencegahan Pencucian Uang dan Uang Haram (Studi Kasus di Perbankan Syari’ah Solo Raya) - Sumadi Sumadi (ITB AAS INDONESIA Surakarta, 2016)
Technological advances and the globalization of financial information, do not always have a positive impact for the community but sometimes it becomes the development of crime, especially white-collar crime (white collar crime), business crime (business crime), or a corporate crime (Corporate crime). Money laundering or commonly known as money laundering, is a method to hide, move, and use the result of a criminal act, the activities of criminal organizations, economic crime, narcotics trafficking, and other activities that constitute criminal activities. Money laundering, essentially involves assets (income / wealth) disguised so that it can be used without being detected that such assets derived from illegal activities. Melaului money laundering income or assets derived from illegal activity is converted into a financial asset that seems to come from a legitimate source / legal. Key Words : Money laundering, Economic syariah, Islamic Bank.